Soil enzyme activity -Dehidrogenase, ß-glucosidase, Phosphatase and Urease- under different crops - Henríquez, Carlos (2014)
The activity of 4 soil enzymes in farms under different agronomic managements and in different soil types was analyzed. The enzymes tested were phosphatase, β-glucosidase, dehydrogenase and urease. Soil samples were taken from the first 20 cm in depth, in order to determine the activity of the 4 enzymes and analyze them chemically. It was found that Dehydrogenase enzyme activity ranged from 0.13 to 4.46 with an average of 1.17 (μg INTF.g - 1 .h -1 ); β-glucosidase enzyme ranged from 31.9 to 208.1 with an average of 108.1 (μg PNP.g -1 .h -1 ). Furthermore, phosphatase had values between 413.4 and 3043.6 with an average of 1521.5 μg PNP.g -1 .h -1 , while Urease ranged from 12.5 to 52.8 with an average of 38.3 μg N-NH4.g -1 .h -1 . Phosphatase correlated with the percentage of organic matter and carbon in the soil (0.75 and 0.76 respectively, p<0.01); an inverse relationship was found between the activity of this enzyme and the content of available P (-0.53r, significant at p<0.10). Urease correlated with phosphatase (r=0.61 p<0.05) and with dehydrogenase (r-0.77 p<0.01). Multivariate cluster analysis based on the enzymatic activity allowed to make similar groups according to the type of crop, which shows the potential of usage that this property has for undertaking more detailed studies.